The first report of the Colchicum ancyrense B.L. Burtt for Khersons’ka oblast’ (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Data about Colchicum ancyrense B.L. Burtt. (Red Data Book of Ukraine) as a new species for the Kherson region are provided.
Keywords: Colchicum ancyrense, steppe slopes, Ingulets River, Arabatskaya Strelka Spit, Biryuchiy island, floristic findings, Kherson region.